Sectoral shocks and monetary policy in the United Kingdom - Huw Dixon; Jeremy Franklin; Stephen Patrick Millard (Cardiff University, Cardiff Business School, 2021)
In this paper, we examine the extent to which monetary policy should respond to movements in sectoral inflation rates. To do this we construct a Generalised Taylor model that takes specific account of the sectoral make-up of the consumer price index (CPI). We calibrate the model for each sector using the UK CPI microdata. We find that a policy rule that allows for different responses to inflation in different sectors outperforms a rule which just targets aggregate CPI, as does a rule that responds only to non food and energy inflation. However, we find that the optimal sectoral rule only leads to a small absolute improvement in terms of extra consumption.
Keywords: E17; E31; E52; 330; CPI inflation; Sectoral inflation rates; Generalised Taylor economy